Efisiensi Pemanfaatan Limbah Domestik Industri Ransum Makanan Hewan Sebagai Penyiraman Ruang Terbuka Hijau - Rintang Wanda Septiyana; Raden Kokoh Haryo Putro (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The animal feed ration industry in South Kalimantan Province produces domestic liquid waste from supporting activities with quite high levels of pollutants. The waste is processed using a Wastewater Treatment Plant (WWTP) and reused to reduce environmental impacts. This study aims to examine the efficiency of utilizing domestic waste as an alternative water source for watering Green Open Spaces (GOS) in industrial areas. The research method used is descriptive-quantitative based on secondary data. Based on the results of wastewater quality measurements at the WWTP outlet,it shows that domestic waste has met the quality standards according to the Minister of Environment and Forestry Regulation P.68 of 2016 and PP No.22 of 2021 for watering purposes. The animal feed ration industry produces domestic waste of 15.5m³/day with a WWTP capacity of 20m³/day and a planned GOS area of ​​8,715.15m². There are two scenarios for wastewater utilization, namely in the dry season with an efficiency of 40.65% and the rainy season with an efficiency of 81.31% of the total industrial raw water needs. These results indicate that domestic waste in the animal feed ration industry has the potential to be an alternative water source that is environmentally friendly and supports sustainable water management.